PERLAKUAN AKUNTANSI TERHADAP PIUTANG TAK TERTAGIH (Studi Kasus pada PT. XYZ di Surabaya) - , Wiratna Wiratna; Dinda Ayu Dilarkarisma (Fakultas Ekonomi Universitas 45 Surabaya, 2020)
Uncollectible Receivables are losses incurred by the company as a result of receivables that are not paid by the debtor. The purpose of this study is to determine the treatment applied to the company on uncollectible accounts carried out at PT. XYZ in Surabaya. The method used in this research is descriptive qualitative method. The results of this study indicate that companies that have implemented the recording of accounts receivable by PT. XYZ properly, with a record as receivables when invoices or passages are issued for goods that have left the warehouse. Suggestions and recommendations that can be given from the implementation of this research are to improve the recording of uncollectible accounts, the company can make a schedule for aging of its receivables so that it can see the amount of receivables that have passed due to payment and also present how much of the receivables cannot be collected based on the age of the accounts. presentations that can be determined by the company based on past experience and previous sales.